Extraction of Arabinoxylans from deoiled rice bran - Shelar, Dhavalkumar N; Patil, Rohit A; Lokhande, Siddharth M; Patil, Shital A; Udachan, Iranna S (Journal of Postharvest Technology, 2024)
This study is focused on the extraction of arabinoxylans (AX) from cereal by-products, with a specificemphasis on deoiled rice bran. The research investigates the influence of various experimental conditions, including the concentrations of sodium hydroxide and sodium chlorite, as well as the temperature, with the goal of optimizing the extraction and delignification process. The optimal conditions were determined to be a 40% sodium hydroxide pretreatment and a 30% sodium chlorite delignification step conducted at a temperature of 60°C, resulting in a consistent 12% yield of purified arabinoxylan. The purified AX exhibited a moisture content of 9.07% and a carbohydrate content of 76.89%. FTIR analysis confirmed the presence of DORB-AX, while TLC and HPLCanalyses identified the presence of arabinose and xylose, with an A:X ratio determined to be 0.58. These findings provide valuable insights into the compositional and structural characteristics of thearabinoxylan sample, which is a significant constituent of cereal grain cell walls, particularly in wheatand rice bran. The methodology presented in this study enhances our understanding of AXextraction and holds promise for potential applications in diverse industrial sectors..
Keywords: De-oiled rice bran (DORB); Alkaline extraction; Arabinoxylan